Risk factors for depression after and ischemic ictus - Herrera, Mercedes (2020)
Objective: To identify risk factors for depression after and ischemic ictus (DII) in adults. Methods: A non-matched case-control study was carried-out including 81 cases and controls, respectively recruited from the neurologic outpatient clinic of Hospital Santa Rosa de Lima from September to December of 2018. Clinical and epidemiological data were gathered and stored in a data base. The Hamilton Depression Rating Scale was used to diagnose depression. Odds rations and 95% CI were calculated and a multivariate logistic regression analysis was used. Results: smoking (OR=4.67; IC95%, 1.99-10.92, p<0.001), lesion located on the left hemisphere (OR=3.11; IC95%, 1.41-6.84, p=0.005) and cognitive deterioration (OR=3.18; IC95%, 1.42-7.10, p=0.005) were independently associated with DII. Conclusions: Smoking, lesions located on the left hemisphere and cognitive deterioration were associated with DII but further studies are needed to elucidate the nature of these associations.